Schisandrin A Inhibits the IL-1β-Induced Inflammation and Cartilage Degradation via Suppression of MAPK and NF-κB Signal Pathways in Rat Chondrocytes - Tu, Chang; Huang, Xiaojian; Xiao, Yifan; Song, Mingyu; Ma, Yongzhuang; Yan, Jiyuan; You, Hongbo; Wu, Hua (Frontiers in Pharmacology, 2019)
Osteoarthritis (OA) is a common joint disease in the elderly population. Its development has been reported to be associated with cartilage degradation and inflammatory responses. Schisandrin A, a bioactive lignin in Schisandra sphenanthera, has shown its anti-inflammatory potential in various inflammation diseases. However, the effects of Schisandrin A on OA remain to explore. In this study, rat chondrocytes were treated with IL-1β (10ng/ml) with or without different concentrations of Schisandrin A for 24 h. Cell viability was evaluated by CCK-8 assay. Production of nitric oxide (NO) and prostaglandin E2 (PGE2) was measured by the Griess reaction and ELISA. The MAPK/NF-κB-related signaling molecules expression and the protein production of inducible nitic oxide synthase (iNOS), cyclooxygenase (Cox)-2, MMPs (MMP1,MMP3,MMP13), ADAMTS5, Collagen II, aggrecan and Sox9 were detected by Western blot. Protein expression of Collagen II, aggrecan and p65 nuclear translocation was evaluated by immunofluorescence. In vivo, intra-articular injection of 50μM Schisandrin A or equal volume of vehicle was performed on rat OA models. Severity of cartilage damage was evaluated by HE and Safranin-O-Fast green staining. Our results revealed that Schisandrin A could suppress the IL-1β-induced production of NO and PGE2 in rat chodrocytes. Consistent with these findings, the upregulation of iNOS and Cox2 could also been decreased by Schisandrin A. Additionally, Schisandrin A could inhibit IL-1β-induced cartilage matrix catabolic enzymes including MMPs and ADAMTS5. Moreover, the IL-1β-induced downregulation of Collagen II, aggrecan and Sox9 could be ameliorated by Schisandrin A. Mechanistically, Schisandrin A functioned by suppressing MAPK and NF-κB signal pathways. In vivo, Schisandrin A prevented cartilage damage in rat OA model. In conclusion, this study elucidates that Schisandrin A inhibits the IL-1β-induced inflammation and cartilage degradation via suppression of MAPK and NF-κB signal pathways, indicating its potential role in OA therapy.